Current status of nurses’ public health emergency response capacity for emerging infectious disease: a cross-sectional study - Qin Qiu; Qin Qiu; Yuntong Liu; Fanping Meng; Fanping Meng; Xinhua Wang; Chunxiang Su (Frontiers in Public Health)
ObjectivesThis study aimed to assess the current status of nurses’ public health emergency response capacity for emerging infectious diseases (EIDs) in tertiary hospitals in Beijing, explore the deficiencies of nurses’ emergency response capacity, and analyze the influencing factors in the post-epidemic era.MethodsA convenience sampling method was utilized to recruit registered nurses in 3 tertiary hospitals in Beijing from 27 August and 2 September 2024. The research team designed a questionnaire that included basic information section and a section of questionnaire on public health emergency response capacity for EIDs. The overall Cronbach’s α of the questionnaire was 0.982. The non-parametric Mann–Whitney U test and Kruskal-Wallis test were employed to assess intergroup differences, subsequently leading to the development of a multiple linear regression model based on the study data.ResultsThe study enrolled 1,484 registered nurses. A total of 1,446 valid questionnaires were maintained, resulting in a 97.4% valid response rate. The median score of nurses’ public health emergency response capacity for EIDs was 177, indicating a modest level of competency. The analysis revealed statistically significant disparities in the scores of the dimensions of nurses’ emergency response competencies (H = 1146.228, p = 0.000). The scores of the dimensions were ranked in ascending order as follows: cognition (median = 3.00, IQR = 2.50–3.20), theoretical knowledge (median = 3.00, IQR = 2.75–3.46), disposal capacity (median = 3.36, IQR = 2.93–4.00), and clinical skill (median = 3.86, IQR = 3.29–4.36). There was a significant difference in scores for nurses’ public health emergency response capacity for EIDs in terms of clinical role (p = 0.008), hospital classification (p = 0.000), and rescue experience (p = 0.000). Multiple regression analysis revealed that the hospital classification and rescue experience of EIDs were the influential factors of nurses’ emergency response capacity (R2 = 0.044, F = 11.023, p < 0.05), and rescue experience significantly predicted emergency response capacity scores.ConclusionThe findings revealed that the nurses’ public health emergency response capacity for EIDs was at a moderate level and the capacity of the dimensions were unbalanced, necessitating targeted improvement. Future initiatives should prioritize strengthening theoretical reinforcement training and cognitive transformation programs for nurses, while accelerating the development of EID specialty nurses and inter-hospital collaboration. Existing training and educational mechanisms require optimization, with particular emphasis on organizational incentives alongside leadership modeling. Ensuring that nurses will have better performance in future public health emergencies for EIDs.